On one Dubinin extreme problem - Zabolotnyi, Ya. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain a particular solution of the known conjecture of V. N. Dubinin about nonoverlapping domains on a complex area.